2011
DOI: 10.1002/adma.201101060
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic and Biologically‐Inspired Computing Using Phase‐Change Materials

Abstract: Phase‐change materials offer a promising route for the practical realisation of new forms of general‐purpose and ‘brain‐like’ computers. An experimental proof‐of‐principle of such remakable capabilities is presented that includes (i) the reliable execution by a phase‐change ‘processor’ of the four basic arithmetic functions of addition, subtraction, multiplication and division, (ii) the demonstration of an ‘integrate and fire’ hardware neuron using a single phase‐change cell and (iii) the expostion of synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
191
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(194 citation statements)
references
References 29 publications
(50 reference statements)
2
191
0
1
Order By: Relevance
“…The restored, re-crystallized pixels look slightly brighter than those crystallized in the first writing. Here we also note that, instead of point-to-point erasing, if necessary, the pattern can be erased in one step by using a single high energy pulse with large hot-spot 29 , dramatically simplifying and speeding up the process. We expect that rates at which pixels can be erased and rewritten should, in principle, be similar to the rates of information storage in DVD technology where the 20 ns recrystallization time in GST allows for bitrates of up to 35 megapixels per second.…”
Section: Dynamically Optically Reconfigurable Zone-plate Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The restored, re-crystallized pixels look slightly brighter than those crystallized in the first writing. Here we also note that, instead of point-to-point erasing, if necessary, the pattern can be erased in one step by using a single high energy pulse with large hot-spot 29 , dramatically simplifying and speeding up the process. We expect that rates at which pixels can be erased and rewritten should, in principle, be similar to the rates of information storage in DVD technology where the 20 ns recrystallization time in GST allows for bitrates of up to 35 megapixels per second.…”
Section: Dynamically Optically Reconfigurable Zone-plate Devicementioning
confidence: 99%
“…When annealed to a temperature between the glass-transition and the melting point, the GST transforms from an amorphous state into a metastable cubic crystalline state, while a short high-density laser pulse melts and quickly quenches the material back to its amorphous phase with a pronounced contrast of dielectric properties observed between the two phases. Although nanosecond and microsecond laser pulses, which provide robust switching between amorphous and crystalline phases, are conventionally used in optical data storage technology, it was recently shown that femtosecond laser pulses can induce multi-level switching 29,30 . In the multi-level regime, metastable semi-crystallized states are created by carefully controlling the energy and the number of stimulating optical pulses.…”
mentioning
confidence: 99%
“…For instance, by comparing the crystallization times of Ge 15 Sb 85 in planar films excited optically and in bridge nanodevices excited electrically, it was shown that optical and electrical properties are interrelated. [10] Furthermore, simultaneous measurements of reflectivity and electrical resistivity of GST thin films during isothermal crystallization showed a decrease in resistivity preceding an increase in reflectivity, explained by the appearance of small crystalline nuclei that enable electrical conduction by percolation prior to the formation of a crystalline region large enough to be optically detectable.…”
Section: Doi: 101002/aelm201700079mentioning
confidence: 99%
“…This property has been referred to as accumulation and occurs by means of optical as well as electrical pulses. [14][15][16] In this work therefore we investigate the phase transition of GST by simultaneously examining the optical and electrical responses of crossbar-type nanoscale devices exposed to cumulative optical and electrical excitations.…”
Section: Doi: 101002/aelm201700079mentioning
confidence: 99%
“…Electrical phase change memories (PCMs) are of much topical interest as a potential next-generation non-volatile memory technology 1,2 and for possible advanced applications in such areas as arithmetic and neuromorphic processing. 3,4 PCMs utilize a reversible switching transition from a high-resistance (amorphous) state to low-resistance (crystalline) state in order to store data. A characteristic feature of the electrically driven amorphous to crystalline (SET) transition is the existence of a threshold electric field that must be exceeded for switching to occur.…”
mentioning
confidence: 99%